The role of unsafe schemas and insecure attachment responses in PTSD symptomatology after traumatic adulthood experiences : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Passmore, Teesha (Massey University, 2002)
The most common disorder resulting from trauma is posttraumatic stress disorder (PTSD). Empirical research affirms the effectiveness of several cognitive-behavioural therapies in treating PTSD symptomatology; however additional complications including interpersonal difficulties, treatment resistance and the simultaneous development of other disorders, such as depression and alcoholism, often impedes the effective treatment of PTSD. The aim of the present study was to provide a deeper understanding of specific cognitive-emotional schemas related to PTSD symptomatology. Unsafe schemas involving perceptions of severe threat regarding a person's sense of safety, control and invulnerability; and internal working models (IWMs) involving generalized attachment related perceptions and feelings regarding the self and others, were the schemas that were investigated. Participants were volunteers from the general community, responding to written or verbal advertisements regarding the study. A total of 188 participants filled out four self-report questionnaires about their own psychological and behavioural responses to a past traumatic event. The questionnaires gathered demographic data, details about the traumatic event and information about the degree to which PTSD symptoms, unsafe schemas and IWMs were elicited. The findings indicated that a threatened sense of control was the highest significant predictor for both intensity and length of time of PTSD symptoms. Although moderately strong significant correlations were found between PTSD symptomatology and the other unsafe schemas (threatened safety and threatened invulnerability) these variables did not predict intensity or length of time that PTSD symptoms were experienced. Negative IWMs of others predicted both intensity and length of time of PTSD, whereas negative IWMs of the self predicted only intensity of PTSD symptoms.Positive IWMs did not significantly predict PTSD symptomatology. Several other statistical comparisons confirmed that unsafe schemas and negative IWMs of others both appear to play a significant role in chronicity of post-traumatic symptomatology. The findings generated several important practical implications for the treatment of traumatized individuals, which were discussed along with limitations of the study and directions for future research. Potential explanations for the findings of the research in relation to previous research findings were also proposed.
Keywords: Post-traumatic stress disorder -- Psychological aspects; Attachment behavior